High resolution continuous record of grain size, magnetic susceptibility, color (a*) of the 20 m thick loess palaeosol sequence of Harletz, Bulgaria - Antoine, Pierre (PANGAEA, 2019)
While numerous high-resolution studies concerning Last Glacial aeolian sequences are available for Europe, the approach of the penultimate glacial in this geographical area is still poorly developed. In order to bridge this gap, this study focuses on the Bulgarian sequence of Harletz, along the Danube River, where extremely high sedimentation rates allow the depiction of high-resolution signals during MIS 6. At Harletz in NW Bulgaria on the western bank of the Ogosta River (tributary of the Danube) a 20m thick loess-palaeosols section was cleaned and sampled for a multi-disciplinary study and detailed pedostratigraphic approach. High-resolution continuous bulk sampling (5 cm) was carried out to characterise sedimentary grain size, magnetic properties (including magnetic susceptibility and its frequency dependence), colour reflectance (1 cm), and organic carbon. Geochronological control is based on 16 samples collected for OSL and MET-pIRIR dating. Using a cyclo-stratigraphic approach of the sequence combined with dating constraints provided by both MET-pIRIR dates and the age of a tephra layer occurring at a depth of 12m within the main loess unit, we can demonstrate that the Harletz section exhibits a 10m thick Late Saalian (Marine Isotope Stage 6, MIS 6) loess accumulation unique in Europe. The lower part of the main loess unit is 4m thick and overlies a basal brown soil complex allocated to MIS 7, which includes an exceptionally thick (4 m) and detailed succession of loess and four incipient soil horizons never described in European loess until now. The closest and best-dated high-resolution palaeoenvironmental archive suitable for comparison comes from Lake Ohrid located about 400 km to the SW of Harletz. The Ohrid palynological record shows a progressive step-by-step evolution in climate and in environmental change during the transition between MIS 7 and MIS 6 from which a parallel with the Harletz pedosedimentary succession can be proposed. During the younger part of MIS 6 (160-129ka), steppe vegetation with abundant herbs (Artemisia) is dominant in the Lake Ohrid record, in good accordance with a global enhancement of aeolian dynamics, especially well recorded in sections located close to the Danube River from Serbia to Bulgaria and Romania (L2 loess). According to interpretations stemming from this study, the silts and fine sands building the Harletz loess section would have been transported from the Danube braided river system located (at that time) at about 4.5 km to the NW. Based on our data, the main loess units are characterised by a very low to a total absence of coarse sand particles. By contrast, during the Eemian interglacial (MIS 5e), and to a lesser extent throughout MIS 5 and during MIS 3 interstadials, the long distance transport of silt and fine sand particles is stopped and a weak aeolian sedimentation is likely driven by north-easterly winds transporting coarse sand grains from the proximal Ogosta River sandy banks. Finally, the weak development of Last Glacial loess (4m max.) likely results from a rapid infilling of the sedimentary trap during the Saalian, then followed by a strong anthropogenic erosion of the topsoil and of the upper part of the loess profile since the Early Holocene (Neolithic).
Keywords: Bulgaria; Grain Size; Harletz; high-resolution; Loess; MIS 6; palaeosols; Saalian